2017
DOI: 10.2507/28th.daaam.proceedings.113
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CAM Strategies on the Tool Wear and Surface Roughness

Abstract: The article deals with the tool life of ball nose end mills and surface roughness of steel C45 depending on contouring and copy milling. The aim was to determine and compare the wear of ball nose end mill and surface roughness parameter for different types of ball end milling strategies, as well as to specify particular steps of the measurement process. For tool life test, DMG DMU 85 monoBLOCK 5-axis CNC milling machine was used. In the experiment, the cutting speeds, feed rates, axial and radial depth of cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In our experiment arithmetical surface roughness -Ra and maximum flank wear -VBmax as a criterion were used. The research follows the author's previous article [15], where was found that contouring had better results than copy milling in specified criteria. In this research we use three best CAM strategies from all tested in previous experiments.…”
Section: Introductionmentioning
confidence: 83%
“…In our experiment arithmetical surface roughness -Ra and maximum flank wear -VBmax as a criterion were used. The research follows the author's previous article [15], where was found that contouring had better results than copy milling in specified criteria. In this research we use three best CAM strategies from all tested in previous experiments.…”
Section: Introductionmentioning
confidence: 83%
“…The element surface quality after milling is one of the key factors. Many authors were raising the problem of machining strategy optimisation as regards the surface quality improvement [13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors researched the surface roughness. Zaujec at all [3] studied the influence of CAM strategies on surface roughness. Hronek & Zetek [4] observed how cutting edge radius influence on surface roughness when milling nickel alloy.…”
Section: Introductionmentioning
confidence: 99%